Antioxidants facilitate high-intensity exercise IL-15 expression in skeletal muscle - Pérez-López, A.; Martin-Rincon, M.; Santana, A.; Perez-Suarez, I.; Dorado, C.; Calbet, J. A. L.; Morales-Alamo, D. (International Journal of Sports Medicine, 2019)
Interleukin (IL)-15 stimulates mitochondrial biogenesis, fat oxidation, glucose uptake and myogenesis in skeletal muscle. However, the mechanisms by which exercise triggers IL-15 expression remain to be elucidated in humans. This study aimed at determining whether high-intensity exercise and exercise-induced RONS stimulate IL-15/IL-15Ra expression and its signaling pathway (STAT3) in human skeletal muscle. Nine volunteers performed a 30-s Wingate test in normoxia and hypoxia (PIO2=75 mmHg), 2 h after placebo or antioxidant administration (a-lipoic acid, vitamin C and E) in a randomized double-blind design. Blood samples and muscle biopsies (vastus lateralis) were obtained before, immediately after, and 30 and 120 min post-exercise. Sprint exercise upregulated skeletal muscle IL-15 protein expression (ANOVA, P=0.05), an effect accentuated by antioxidant administration in hypoxia (ANOVA, P=0.022). In antioxidant conditions, the increased IL-15 expression at 120?min post-exercise (33%; P=0.017) was associated with the oxygen deficit caused by the sprint (r=-0.54; P=0.020); while, IL-15 and Tyr705-STAT3 AUCs were also related (r=0.50; P=0.036). Antioxidant administration promotes IL-15 protein expression in human skeletal muscle after sprint exercise, particularly in severe acute hypoxia. Therefore, during intense muscle contraction, a reduced PO2 and glycolytic rate, and possibly, an attenuated RONS generation may facilitate IL-15 production, accompanied by STAT3 activation, in a process that does not require AMPK phosphorylation.